The New Gnosis and the Denial of Ontological Differences - Jesús Ballesteros (Ius Humani. Jornal do direito, 2021)
The current transhumanist or posthumanist movements continue the thesis of the old gnosis devaluing the creation like something imperfect. Its novelty is to believe in the possibility of overcoming the creation thanks to technology (biotechnology and bionics). The ideology of gender partly anticipates this way of thinking by devaluing the somatic difference between male and female. This denial of the differences then applies to those existing between the human and the non-human (on one side the primates, and on the other the computer). Posthumanism and transhumanism believe that technology will not only overcome the ontological differences, which form the human, but also the so-called extreme situations, such as illness, suffering and death itself. In this case, by copying the brain information as software to a hard disk. The intellectual myopia of these movements is clear: they reduce the scope of knowledge to mere genetic or electronic information, denying knowledge and, more importantly, wisdom. Their current success is due to their connection with the central thesis of financial capitalism: the need for total manipulation of the real and indefinite growth. Far from advancing the human being, they create malfunctions.